Not All Citations Are Equal: Reflections from Medical Anthropology in the Philippines - Lasco, Gideon (Archīum Ateneo, 2023)
Long before recent calls to decolonize anthropology, practitioners of “national anthropologies”—such as local anthropologists from/in/of the Philippines—have sought to implement a more inclusive kind of scholarship, and this has been reflected in their citational practices. Indeed, a look at the scholarly output of Philippine anthropologists would show a diverse set of citations that feature local scholarship, including those written in Filipino. As I will show in this article, however, not all citations are equal. Theoretical and methodological citations are typically drawn from Euro-American scholars while scholarship from the Global South is typically invoked as illustrative examples, as parallels, and to set context. Such citational practices, I argue, are a consequence of particular disciplinary histories and divergent priorities. They reinforce the inequalities of power and academic capital within medical anthropology, raising the need for more reflexivity not just about whom medical anthropologists cite but for what reasons.